DETERMINANTS OF POST-PREGNANCY PSYCHOLOGICAL ADJUSTMENT OF OUT-OF-SCHOOL TEENAGE MOTHERS IN SOUTH-WEST NIGERIA (2015)
Transition to motherhood generally represents a major developmental milestone for all women even though it could be stressful for teenagers; because the basic physiological features for coping with pregnancy are not yet fully developed. Pregnancy, most especially among teenagers, could therefore be psychologically debilitating, physically frustrating and emotionally draining; particularly when the teenager is out-of-school. Although there are related studies on post-pregnancy psychological adjustment of women generally, only few of such studies concentrated on teenagers who are out-of-school. This study, therefore, investigated stigmatisation, social support, family support, peer support, self-esteem, self-concept, sexual debut, depression and socioeconomic status as determinants of post-pregnancy psychological adjustments of out-of-school teenage mothers. The study adopted descriptive survey design of ex-post facto type. The purposive sampling technique was used to select 42 Local Government Areas (LGAs) across Lagos (eight), Ondo (seven), Oyo (seven), Ogun (seven), Osun (seven) and Ekiti (six) where there is high prevalence of out-of-school teenage mothers. Also, the purposive sampling technique was used to select the main health centre in each of the selected LGAs. One thousand, two hundred and ninety two out-of-school teenage mothers attending post-natal clinic across the 42 health centres were purposively selected. Duke-UNC Functional Social Support Questionnaire (r=0.72),Teenage Mothers Post-Pregnancy Psychological Adjustment (r=0.82), Rosenberg Self-esteem (r=0.74), Self-Concept Clarity (r=0.88), Global Depression (r=0.79), Teenage Mother Stigmatisation (r=0.76), Teenage Mother Sexual Debut (r=0.78), Teenage Mother Peer Influence (r=0.72), Family Support (r=0.86) and Socio-Economic Status (r= 0.64) scales were used for data collection. These were complemented with six Focus Group Discussions sessions with selected 72 teenage mothers. Three research questions were answered and nine hypotheses tested at 0.05 level of significance. Data were analysed using descriptive statistics, Pearson product moment correlation, multiple regression and content analysis. Participants were secondary school drop outs with a mean age of 14 ± 3 years. There was a significant multiple correlation between the independent variables and post-pregnancy psychological adjustments of out-of-school teenage mothers (F(9;1282)=29.07; R=0.41) and accounted for 16.4% of its variance. Self-esteem (β=0.296), social support (β=0.13), stigmatisation (β=0.09), self-concept (β=0.08), peer influence (β= 0.06) had positive significance contributions with post-pregnancy psychological adjustments while socio-economic status (β= -0.14), depression (β=-0.13) and sexual debut (β=-0.01) had significant negative contributions but family support had none. Self-esteem (r=0.34), social support (r=0.22), self-concept (r=0.21), stigmatisation (r=0.21), peer influence (r=0.19), sexual debut (r=0.15) and depression (r=0.09) had significant correlations with post-pregnancy psychological adjustments. Teenage-motherhood among the respondents was more of a chain of action, which they imitated from their mothers/sisters and perceived as a way of life. Self-esteem, social support, stigmatization, self-concept and peer influence were the potent predictors of post-pregnancy psychological adjustment of out-of-school teenage mothers in South-West Nigeria. Counsellors and educational psychologists should integrate these factors into intervention programmes targeting out-of-school teenage mothers. Keywords: Out-of-school teenage mothers, Post-pregnancy psychological adjustment, Psycho-social variables, South-West, Nigeria Word count: 454